Penyuntingan Kalimat Aktif dan Pasif dalam Buku Ajar Bahasa Indonesia Kelas I SD Kurikulum Merdeka: Studi Kasus pada Buku Aku Bisa! - Jasmin Fauzia; Cantika Kunthi Prabandari; Laila Nurmayanti; Mohamad Afrizal (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the use of active and passive sentences in the Bahasa Indonesia: Aku Bisa! textbook used in Grade 1 of elementary school under the Merdeka Curriculum. Textbooks play an important role in the learning process, particularly as examples of proper and correct language use for students. This research employs a descriptive qualitative approach using documentation techniques to identify and analyze sentence structures based on appropriate linguistic rules. The main focus of the study is to reveal the forms of active and passive sentences used, and to assess their accuracy in terms of structure and appropriateness for young learners' language development. The findings show that some sentences are structurally inaccurate, overly complex, or misaligned with the cognitive development of first-grade students. Such issues can hinder students' understanding of the learning material. Therefore, editing is necessary to simplify and correct sentence structures so that they are more communicative and easier to understand. This study emphasizes the importance of the editing process in textbook development to ensure high linguistic quality, support effective learning, and align with the principles of the student-centered Merdeka Curriculum.